2019
DOI: 10.21203/rs.2.15453/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mating precedes selective immune priming which is maintained throughout bumblebee queen diapause

Abstract: Background: Understanding the mechanisms by which organisms adapt to unfavourable conditions is a fundamental question in ecology and evolutionary biology. One such mechanism is diapause, a period of dormancy typically found in nematodes, fish, crustaceans and insects. This state is a key life-history event characterised by arrested development, suppressed metabolism and increased stress tolerance and allows an organism to avoid prolonged periods of harsh and inhospitable environmental conditions. For some spe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
5
1
Order By: Relevance
“…Together with findings from other studies, these data show that shifts in queens’ physiological quality, as well as the interaction between nutritional status and age ( Costa et al ., 2020 ), may influence diapause survival. While the queens in our study were unmated ( Baer et al , 2005 , Colgan et al , 2019 ), previous research in B. terrestris queens found that, on average, unmated queens survived only 5 days longer as compared to mated queens in cold storage ( Greeff et al ., 2008 ). Therefore, the lack of mating is unlikely to significantly affect our data on queen survival.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Together with findings from other studies, these data show that shifts in queens’ physiological quality, as well as the interaction between nutritional status and age ( Costa et al ., 2020 ), may influence diapause survival. While the queens in our study were unmated ( Baer et al , 2005 , Colgan et al , 2019 ), previous research in B. terrestris queens found that, on average, unmated queens survived only 5 days longer as compared to mated queens in cold storage ( Greeff et al ., 2008 ). Therefore, the lack of mating is unlikely to significantly affect our data on queen survival.…”
Section: Discussioncontrasting
confidence: 65%
“…Both types of proteins are critical for dealing with stressors associated with diapause, such as cold stress and starvation. However, a more detailed analysis of the proteins present in the hemolymph pre-diapause [see ( Colgan et al ., 2019 )] could be informative to understanding which stressors queens are equipped to mitigate during diapause (e.g. temperature stress or pathogens) and which stressors are more likely to result in queen mortality.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that mating may also influence the immune system of queens. Molecular evidence has suggested that mating prior to overwintering for B. terrestris resulted in elevated levels of antimicrobial peptides, and these peptide levels were maintained throughout overwintering [ 112 ]. Conversely, comparisons between virgin and mating queens have found that mating significantly increases the incidence of melanized spermatheca, which may indicate pathogen transfer during mating [ 111 ].…”
Section: Queen Success As a Results Of Matingmentioning
confidence: 99%
“…However, post-hibernation they face significant exposure as they forage for resources before and while founding their colony. Interestingly, mating and hibernation drive changes in gyne immunity (Barribeau and Schmid-Hempel 2017;Colgan et al 2019) and gut microbiome (Wang et al 2019), both of which could influence interactions between gynes and C. bombi. Further work should examine their susceptibility to infection, in comparison to gynes, and its relation to immunity.…”
Section: Discussionmentioning
confidence: 99%